The Influence of Customer Relationship Management, Brand Image, and Service Quality on Patient Satisfaction at the Exec - Wijayanti, Endry; Kustiningsih, Nanik; Rahayu, Sri (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the influence of Customer Relationship Management (CRM), brand image, and service quality on patient satisfaction at the Executive Clinic of Siti Khodijah Hospital, Sidoarjo. The research adopts a quantitative approach with a survey method, involving patients who have received services at the Executive Clinic as respondents. Data were collected through questionnaires and analyzed using multiple linear regression techniques.The results indicate that CRM, brand image, and service quality significantly and positively impact patient satisfaction, both partially and simultaneously. Among these factors, service quality is identified as the most dominant variable influencing patient satisfaction. The findings emphasize the importance of maintaining effective customer relationship management practices, building a strong brand image, and ensuring high-quality services to enhance patient satisfaction.These results provide valuable insights for hospital management to develop strategies that prioritize patient-centered care, strengthen brand positioning, and improve service delivery at the Executive Clinic. Further research is recommended to explore other variables that may affect patient satisfaction in different healthcare settings.